Phenolic profiling of Piper species by Liquid Chromatography-Mass Spectrometry - Zachariah, D Sruthi, T J (Journal of Spices and Aromatic Crops, 2016)
In the present study, phenolic compounds from four Piper species viz., P. nigrum (Black pepper), P. longum, P. chaba and P. colubrinum were identified by LC-MS analysis. The identified phenolic compounds mainly include phenolic acids and flavonoids. Thirteen compounds were identified in black pepper which mainly included hydroxybenzoic acids (syringic acid, protocatechuic acid etc.), hydroxycinnamic acids (caffeic acid, ferulic acid and 4-coumaric acid) and flavonoids (luteolin-8-C-glucoside and apigenin). Among the six compounds identified in P. longum, three belonged to hydroxybenzoic acid and the other three belonged to hydroxycinnamic acid category. Seven compounds were identified from P. chaba which comprised of hydroxybenzoic acids, phenolic aldehydes and hydroxycinnamic acids. In P. colubrinum, ten compounds were identified and majority were flavonoids like kaempferol-5-glucoside and apigenin-7-galactoside. Hydroxybenzoic acids like protocatechuic acid and phenolic aldehyde like vanillin were also identified in P. colubrinum. Salicylic acid, a monohydroxybenzoic acid was identified in all the four species.